Strong convergence for nonexpansive mappings by viscosity approximation methods in Hadamard manifolds - Kumari, Mandeep; Chugh, Renu (International Journal of Applied Mathematical Research, 2015)
In 2010, Victoria Martin Marquez studied a nonexpansive mapping in Hadamard manifolds using Viscosity approximation method. Our goal in this paper is to study the strong convergence of the Viscosity approximation method in Hadamard manifolds. Our results improve and extend the recent research in the framework of Hadamard manifolds.